2016
DOI: 10.1111/gfs.12264
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis, biomass and nutritive value of Panicum maximum under different shade levels and fertilizer nitrogen rates

Abstract: Panicum maximum is important for cattle production in tropical regions, and it responds well to nitrogen (N) fertilization. Many cultivars have exhibited potential for use in silvopastoral systems, although there is limited information on how different levels of N can influence plant growth and nutritive value under shading. Morphogenetic and structural traits, biomass production and nutritive value of two P. maximum cultivars (Tanzânia and Massai) were investigated under three shading levels (0, 37 and 58%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
3
25

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 40 publications
9
63
3
25
Order By: Relevance
“…Therefore, when selecting herbage species for silvopastures, the potential beneficial effects of complementarity in species mixtures to ameliorate contrasting effects of stressing factors (Nicodemo et al., ) should also be further assessed in subsequent studies. In the case of the Centrosema genotypes tested in this study, with contrasting acclimation strategies to shade and seasonal drought (Guenni et al., ), they may be combined with medium shade‐tolerant C 4 grasses like Brachiaria decumbens (Gómez et al., ) and Panicum maximum (Paciullo et al., ) to improve herbage quality and persistence of understory pastures in silvopastoral systems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when selecting herbage species for silvopastures, the potential beneficial effects of complementarity in species mixtures to ameliorate contrasting effects of stressing factors (Nicodemo et al., ) should also be further assessed in subsequent studies. In the case of the Centrosema genotypes tested in this study, with contrasting acclimation strategies to shade and seasonal drought (Guenni et al., ), they may be combined with medium shade‐tolerant C 4 grasses like Brachiaria decumbens (Gómez et al., ) and Panicum maximum (Paciullo et al., ) to improve herbage quality and persistence of understory pastures in silvopastoral systems.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from the calculation of the proportion of leaves in the total dry mass revealed that the proportion of leaf blades in the dry mass was 21% higher in the SPS than in the OP (29% vs. 24% leaf blades, respectively, for SPS and OP). In fact, shading induces morphological changes in the pasture in order to increase light uptake (Paciullo et al., ). This result can be associated with small magnitude of differences between systems in heifers weight gain, during experimental period, because the higher leaf blade proportion may have contributed positively to animal nutrition in SPS, despite lower forage mass, tiller population density and forage bulk density in this system than in OP.…”
Section: Discussionmentioning
confidence: 99%
“…Paciullo et al. () have suggested that an option for sustainable livestock production is the adoption of silvopastoral system (SPS). Among the productive and environmental benefits of the SPS, the following stand out: Improved soil nutrient availability, increased animal production associated with thermal comfort, and higher crude protein (CP) content of forage, as well as the possibility of income diversification in the property (Baliscei et al., ; Kyriazopoulos, Abraham, Parissi, Koukoura, & Nastis, ; Murgueitio, Calle, Uribe, Calle, & Solorio, ; Paciullo et al., ), and environmental services, such as increased biodiversity, sequestration of atmospheric carbon and mitigation of greenhouse gases (Alves, Madari, & Boddey, ; López‐Carrasco, López‐Sánchez, San Miguel, & Roig, ).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated crop‐livestock‐forestry systems are efficient land‐management alternatives for restoring degraded pastures, increasing food security and promoting carbon sequestration (Dias‐Filho, ; Moraes, Carvalho, Lustosa, Lang, & Deiss, ; Paciullo et al., ; Santos et al., ). However, as the forage grass species planted in integrated systems may be subjected to light restriction, imposed by agricultural crops or tree species, it is necessary to know their agronomic performance under shade, to define their potential use in these systems (Dias‐Filho, ; Gomez, Guenni, & Bravo De Guenni, ; Paciullo et al., ; Pimentel et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic plasticity relates to the species adaptability to changes in the environment, such as variations in solar radiation, temperature, soil water and nutrient availability (Gomez et al., ; Valladares, Laanisto, Niinemets, & Zavala, ). Shade tolerant plants can adjust their morphophysiology, such as biomass allocation pattern, chlorophyll content and leaf area and thickness to maximize light capture (Paciullo et al., ; Valladares et al., ).…”
Section: Introductionmentioning
confidence: 99%